Using Holt Winter 2 Variable Modelling To Analyze The Potential Combining Of Zakat Collection In Three Countries In Southeast Asia As One Business Centre - Muhammad Marizal; Afrizal Mansur; Ibrahim Sulaiman Hanaish; Jamaluddin Jamaluddin; Zikri Darussaamin; Kasmuri Kasmuri; Saifullah Saifullah (Journal of Applied Engineering and Technological Science (JAETS), 2023)
The Covid 19 outbreak has taught businesses all over the world that they must have a business that can not only survive but also thrive in the face of the pandemic. The income from the Zakat, which is one of Islam's teachings about stable business, tends to rise despite the pandemic. As most Muslim countries on the planet, Indonesia, Malaysia, and Singapore have shown that their Zakat Organization, which is utilized to gather gifts from the public every year, expanded dramatically during the pandemic. The primary focus of this investigation will be the data on annual income from Indonesia, Malaysia, and Singapore, three of the world's most Muslim nations. The fact that some businesses will always be loyal to the government is the foundation of the statistical modeling theory that aims to predict the annual zakat income in five and ten years. Holt Winter's statistical modeling of two variables will be used to guarantee accurate forecasting. It accurately generates comparable annual data for the three nations. Likewise, that might act as a strong starting point for using measurable displaying to gauge the zakat gathered in the resulting five and a decade. The zakat revenue will continue to significantly rise in each nation as the study concludes. This result also indirectly demonstrated that businesses in every nation will be able to combine zakat as a blessing without experiencing deflation in Southeast Asia